GLOCALIZATION IN TEACHING LITERAL READING: BRIDGING GLOBAL CONTENT WITH LOCAL CONTEXTS - Ana Wiyasa Nugrahawat (2024)
This study investigates the application of glocalization in the teaching of literal reading comprehension. Glocalization, a concept merging global and local perspectives, is gaining prominence in language education. By blending globally recognized literary works with local cultural contexts, educators aim to create a more engaging and relevant reading experience for students. This abstract investigates into the theoretical foundations of glocalization and provides practical insights into its implementation in reading instruction. This research is conducted in English education program study. The method of this research is qualitative descriptive research. The researcher found the data through interview, observation, and document analysis. The researcher observed and interviewed the participant about the local context in teaching learning activities. The participants are the lecturer and 30 (thirty) students. Drawing on examples from diverse educational settings, it highlights the benefits of glocalization in developing students' literal reading skills and supporting intercultural competence. Through glocalization, educators bridge the gap between global content and local contexts, empowering students to critically engage with texts while appreciating their own cultural identities